Sociolinguistics Analysis on Language Style in Niki Songs - Pangaribuan, Khatleen; Marpaung, Marlin Steffi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Sociolinguistics enables us to comprehend how the language reflect and even shape evolving relationships and ways of interaction in a society. This study is focusses on the language style used on Niki songs. The aim of this study is to find out the differences and similarities of the language style used in “Backburner” and “Anaheim” songs, and to determine the most dominating type of language style used based on Martin Joos’ theory. A descriptive qualitative research technique was used to analyze the data in this study. The data being examined is from Niki’s songs. The result of the study showed three language styles are utilized in "Backburner" out of a total of 28 data points: consultative style (9 data, 32%), casual style (12 data, 43%), and intimate style (7 data, 25%). On the other hand, there are three language styles utilized in "Anaheim" out of a total of 35 data: consultative style (11 data, 31.5%), informal style (11 data, 31.5%), and intimate style (13 data, 37.5%). Furthermore, the most dominating style employed in "Backburner" is casual, while "Anaheim" is intimate, and both songs have an overall informal style.